Application of the Hybrid Bond Graphs and Orthogonal Rational Filters for Sag Voltage Effect Reduction - Trajkovic, D.; Nikolic, V.; Antic, D.; Nikolic, S.; Peric, S. (Elektronika ir Elektrotechnika, 2013)
This papers presents the application of hybrid bond graphs in modeling and simulation of submersible pump in water factory NAISSUS in Nis. The obtained model is used as plant model for control problem reflected by voltage sag effect, caused by starting large motors. In order to improve the performances of pump, we introduce the new control method based on the orthogonal filters of Muntz- Legendre type. The genetic algorithm is used to obtain the parameters needed for filter realization. Finally, the simulation results confirmed good system performances of the given control and it is shown that voltage sag effect is significantly reduced. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.1746